Pengenalan Mobil Pada Citra Digital Menggunakan HOG-SVM - Derry Alamsyah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2017)
The image data on a highway has been available on several online sites. It can be used to pull some information such as traffic congestion, vehicle volume per day, etc. To obtain this information required basic information such as the introduction of the vehicle, in this case the car. The introduction of the car is done by utilizing the features that form the image Histogram of Oriented Gradient (HOG). The introduction of a car based on this feature is done by using a model of linear equations formed from the algorithm Support Vector Machine (SVM), which is a binary classification. The accuracy of the results obtained in this study was 82, 5%